IDENTIFIKASI STRUKTUR EKONOMI SEKTORAL DAN REGIONAL SELURUH PROVINSI DI INDONESIA MENGGUNAKAN ANALISIS NETWORK - Lamtutur Sri Paulina Pasaribu (Center for Economic Studies Universitas Katolik Parahyangan, 2023)
This study aims to identify key sectors in the economy of all provinces in Indonesia by network analysis using Indonesia's Inter-Regional Input-Output (IRIO) tables. The results of this study show that the most sensitive sector and the sector with the highest ranking in terms of having relationships with other important sectors are the manufacturing industry and its region is dominated by provinces on the island of Java. Furthermore, the sectors with the highest ratings in terms of their ability to influence resources among other sectors are the manufacturing, construction, transportation, and warehousing industries, and financial services and insurance sectors. As well as the results of community detection show that sectors that are in the same province and have close geographical distances tend to interact more often. The results of this study also show that the highest rankings of the sector as a whole are dominated by provinces on the island of Java while the lowest is by the Eastern Part of Indonesia.